PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KIMIA SISWA KELAS X DI SMAN 6 MATARAM - Rauhul Jannah; Baiq Sri Ayu Husniarti; Yunita Arian Sani Anwar (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
This classroom action research aims to improve the learning activities and chemistry learning outcomes of students in class X SMAN 6 Mataram academic year 2023/2024 on the topic of chemical compound nomenclature and reaction equations by the implementation of differentiated process learning strategies. This research activity is conducted in 2 cycles each consisting of two meetings, including conducting evaluations at the end of each cycle. Each cycle consists of planning, implementing actions, observation, evaluation, and reflection. The data collected in this research includes qualitative data in the form of observation sheets and quantitative data in the form of student learning outcomes from 34 samples consisting of 17 male and 17 female students. The result of this result indicates an increase in student learning activities score from cycle I to cycle II with an average score of student learning activities respectively 11,25 and 12,9 which are in the active category. Meanwhile, student learning outcomes increased from cycle I to cycle 2 with a classical completeness score of 59,25% successively increasing to 85,3% in cycle II. Based on the results obtained, it can be concluded that the application of differentiated learning (process) can improve the activities and learning outcomes of chemistry students in class X at SMAN 6 Mataram.